Analisis Kasus dan Strategi Optimalisasi Pada UMKM SYF EAU DE PARFUME : Study Kasus Untuk Meningkatkan Kinerja Usaha - Setiawan; Aldy Khusairi, Mhd; Alvin, Mhd; Mardhiyah, Ainun (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Micro, Small, and Medium Enterprises (MSMEs), especially SFY Eau de Parfume, have an important role in supporting the Indonesian national economy. MSMEs contribute more than 60% to Gross Domestic Product (GDP) and provide employment for more than 90% of the workforce in Indonesia. SFY Eau de Parfume is one of the players in the fragrance industry that produces high-quality perfumes at affordable prices. However, this company faces various challenges in facing tight competition, such as rapid changes in consumer preferences, limited capital, limited access to technology, and the need to create innovative marketing strategies. This study aims to identify internal and external factors that affect the performance of SFY Eau de Parfume in facing competition in the perfume market. The focus of the analysis includes challenges in marketing, operational, and product innovation aspects. The results of this study are expected to provide applicable strategic recommendations for SFY Eau de Parfume to improve competitiveness, operational efficiency, and business sustainability. Through the use of digital technology and consumer-based marketing approaches, companies are expected to expand market reach, understand consumer needs more deeply, and develop innovative products to meet evolving consumer preferences.